Disobedient creativity: transversal processes and habitations - Vasconcelos, Flávia Pedrosa (Farol, 2024)
This work weaves a conversation that dwells from a walk between concepts that involve university teaching, in which powers are revisited and not only one point of view is observed, allowing the crossing of ideas and connections, understanding the role of the past and history in the production of knowledge. In this sense, it reflects on the environment in which teaching, research and extension are developed, indicating the role of creative thinking and practice and conceptualizing from collaborative constructions from 2020 to 2024 of the Laboratory of Creativity and Innovation in Visual Arts - LACRIA and the Visual Arts and Creativity Research Group - AVEC - CNPq of the Federal University of Santa Maria - UFSM. Therefore, it understands the contemporary challenge of promoting creativity and the role of memory and history, reviewing them in a posture of disobedient creativity.